INFLUENCE OF INTERNAL ORGANIZATION FACTORS ON TRANSFORMATION OF STATE CORPORATIONS IN KENYA: A CASE STUDY OF KENYA MEDICAL SUPPLIES AUTHORITY - Rosana, Beatrice; Atikiya, PhD, Dr. Rukia (European Journal of Business and Strategic Management, 2019)
Purpose: Internal and external environment affect the way in which organizations operate. Over time organizations have reengineered their operations so as to survive and adapt to the changing situations. The research study underlying objective was to determine the effects of internal organizational structure on transformation of state parastatals in Kenya with reference to KEMSA as study case. Methodology: The study sample was 160 respondents that were randomly selected from a target population of 270 staff at KEMSA. A stratified sample of 160 personnel selected from a population of 270 permanent staff of KEMSA. A sample was collected from each of the three stratums using simple random sampling. Research questionnaires were used to collect data. The research used descriptive statistics and inferential statistics for data analysis. Results: The study findings showed that there is a significant relationship between organizational transformation and the four variables; Organizational structure, Organizational resources, adoption of ICT and Strategic planning. This therefore implies that organizational structure, organizational resources, adoption of ICT and strategic planning affects organizational transformation. A unit increase will improve the organizational transformation in the company. Unique Contribution to Theory, Practice and Policy: The study recommends that for sustainable improvement the KEMSA board of management should manifest to the staff an organization culture that aligns itself to organization structure and ensure proper management of resources. They should also clearly spell out the organization strategy that focuses more on following the organization mission that ensures that staff are conversant with organisation mission and vision.